Diseño de una crema cosmética a partir del aceite obtenido de las semillas de moringa oleifera lam (moringa). - Cayambe Aviles, Katherine Elizabeth (2015)
The seed oil of Moringa oleifera Lam (moringa) has a profile of nutrients, particularly fatty acids which 68.9% is oleic acid which is an excellent alternative to improve the hydration and nutrition of the skin. Therefore the aim of this study was to design a cosmetic cream from oil seed Moringa oleifera (moringa). To start a detailed research study was conducted raw materials used for the formulation, mainly oil, which first proceeded to the collection of seeds considering only those found in good condition and not affected by insect pests or other foreign matter, were used for the extraction of oil by Soxhlet method.